Cancer panel analysis of circulating tumor cells in patients with breast cancer - Lee, Cham Han (Oncol Lett, 2018)
Liquid biopsy using circulating tumor cells (CTCs) is a noninvasive and repeatable procedure, and is therefore useful for molecular assays. However, the rarity of CTCs remains a challenge. To overcome this issue, our group developed a novel technology for the isolation of CTCs on the basis of cell size difference. The present study isolated CTCs from patients with breast cancer using this method, and then used these cells for cancer gene panel analysis. Blood samples from eight patients with breast cancer were collected, and CTCs were enriched using size-based filtration. Enriched CTCs were counted using immunofluorescent staining with an epithelial cell adhesion molecule (EpCAM) and CD45 antibodies. CTC genomic DNA was extracted, amplified, and screened for mutations in 400 genes using the Ion AmpliSeq Comprehensive Cancer Panel. White blood cells (WBCs) from the same patient served as a negative control, and mutations in CTCs and WBCs were compared. EpCAM(+) cells were detected in seven out of eight patients, and the average number of EpCAM(+) cells was 8.6. The average amount of amplified DNA was 32.7 µg, and the percentage of reads mapped to any targeted region relative to all reads mapped to the reference was 98.6%. The detection rate of CTC-specific mutations was 62.5%. The CTC-specific mutations were enhancer of zeste polycomb repressive complex 2 subunit, notch 1, AT-rich interaction domain 1A, serine/threonine kinase 11, fms related tyrosine kinase 3, MYCN proto-oncogene, bHLH transcription factor, APC, WNT signaling pathway regulator, and phosphatase and tensin homolog. The technique used by the present study was demonstrated to be effective at isolating CTCs at a sufficiently high purity for genomic analysis, and supported the use of comprehensive cancer panel analysis as a potential application for precision medicine.